Validation of New Interactive Nutrition Assistant - Diet in India Study of Health (NINA-DISH) FFQ with multiple 24-h dietary recalls among pregnant women in Pune, India. Issue 8 (28th October 2021) - Rajagopalan, Kripa; Alexander, Mallika; Naik, Shilpa; Patil, Nikhil; Mehta, Shivani; Leu, Cheng-Shiun; Bhosale, Ramesh; Mathad, Jyoti S.; Caulfield, Laura E.; Gupta, Amita; Talegawkar, Sameera A.; Shivakoti, Rupak
Abstract: Adequate dietary intake is critical to prevent adverse pregnancy outcomes. India has a high burden of maternal and child morbidity and mortality, but there is a lack of adequate tools to assess dietary intake. We validate an FFQ, New Interactive Nutrition Assistant - Diet in India Study of Health (NINA-DISH), among pregnant women living with and without HIV in Pune, India. Women were selected from a cohort study investigating immune responses to HIV and latent tuberculosis during pregnancy. The FFQ was administered during the third trimester and validated against multiple 24-h dietary recalls (24-HDR) collected in second and third trimesters. Data for analysis were available from fifty-eight women out of seventy enrolled into this sub-study, after excluding those with incomplete data or implausible energy intake. The median (Q1, Q3) age of study participants was 23 (20, 25) years. Median (Q1, Q3) daily energy intakes were 10 552 (8000, 11 958) and 10 673 (8510, 13 962) kJ by 24-HDR and FFQ, respectively, with FFQ overestimating nutrient intake. Pearson correlations between log-transformed estimates from FFQ and 24-HDR for energy, protein, carbohydrate, fat, Fe and Zn were 0·47, 0·48, 0·45, 0·33, 0·4 and 0·54, respectively. Energy-adjusted and de-attenuated correlations ranged from 0·41 (saturated fat) to 0·73 (Na). The highest misclassification into extreme tertiles was observed for fat (22 %), saturated fat (21 %) and Na (21 %). Bias existed at higher intake levels as observed by Bland–Altman plots. In conclusion, NINA-DISH is a valid and feasible tool for estimating dietary intakes among urban pregnant women in Western India.